Emerging Retail Business: Boon for Indian Economy - Singh, Naib (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Indian retail business is growing at very fast rate in the country. This business occupiesa great place of importance in the economy by holding fourth rank in the category of most attractive nations for retailing business. This sector is providing employment to the eight percent employable people. It has been observed that in 2018 Indian retailbusiness will attain the business of US 950 billion. In 2015 Indian retail business is expected to attain the growth rate of 14% to 15%. The future of this sector is very brightand the retail business will certainly be a boon for the Indian Economy.